The Impact of the COVID-19 Pandemic on Consumer Behavior—Evidence From China's Stock Market - Lu, Zhou; Zhu, Linchuang; Li, Xiaoxin; Li, Zhenhui (Frontiers in Public Health, 2022)
The COVID-19 pandemic has dramatically reshaped consumer shopping behavior. Changes in consumer shopping behavior have had a huge and far-reaching impact on the retail industry. Although the existing literature provides investigation on the impact of the epidemic on the retail industry, very few studies discuss the impact of changes in consumer shopping behavior on the stock market performance of the retail industry. This paper selects China's representative retail listed companies. To overcome the problems of the Chow test, the Quandt-Andrews test was used to identify structural change points in the stock prices of listed companies from China’s retail industry during the epidemic. The results suggest that there has indeed been an industry-wide structural change in the stock performance of Chinese retail companies during the pandemic. The study found that the dates of structural mutation of the selected companies were concentrated in the first half of 2020, when the epidemic in China was more severe. Our survey shows that under strict epidemic prevention and control measures, consumers have gradually adapted to the new normal of epidemic prevention to a certain extent, established safety awareness, and changed their consumption behavior. They no longer rely on offline purchases, but greatly Tendency to move to an online purchasing model.